(untitled) (Bangladesh Journal of Urology, 2023)
Background: The concept of clean intermittent self-catheterization (CISC) after optical internal urethrotomy has been regarded as preventive management for bulbar urethral stricture recurrence. Starting date of CISC, total duration of CISC, catheter size and material, and lubricating preparations for the catheter of CISC after OIU have been investigated in several studies to correlate and modify stricture recurrence. But doing CISC by an optimal frequency is still an unsettled issue. Some studies recommended doing this preventive procedure more frequently and some preferred a less intense course of frequency. But patients may find it difficult to follow a daily self-catheterization frequency. Moreover, effect and complications of doing clean intermittent self-catheterization after optical internal urethrotomy has been investigated insufficiently for primary bulbar urethral stricture in existing literatures. So, this study investigated whether CISC biweekly was more beneficial than daily after OIU for primary bulbar urethral stricture.Objective: To compare the effect of doing clean intermittent self-catheterization twice weekly and daily after optical internal urethrotomy for primary bulbar urethral stricture.Materials and methods: This was a hospital based quasi-experimental study among study samples who were selected for optical internal urethrotomy with diagnosed primary bulbar urethral stricture of ≤1.5 cm in length and conducted from November, 2020 to February, 2022 in the Department of Urology, Bangabandhu Sheikh Mujib Medical University. Fifty four study subjects were selected by purposive sampling. After first postoperative week of optical internal urethrotomy, patients attended to learn clean intermittent self-catheterization with a 14 Fr Nelaton Polyvinyl chloride catheter on outdoor basis. They were divided into two groups: Group-A did CISC twice weekly and Group-B practiced CISC daily. Both groups were instructed to do CISC for 6 months. Any patient reported complications associated with CISC (UTI, epididymo-orchitis, per-urethral bleeding, hematuria, urethral pain) were evaluated and treated during this period. After completion of 6 months, both groups had stopped doing CISC. Out-patient follow–up had been performed in both groups at 3 and 7 months to compare International Prostate Symptom Score (IPSS), maximum urinary flow rate (Qmax) by uroflowmetry, post void residual urine (PVR) by ultrasonography and stricture recurrence by retrograde urethrography. Four patients were lost during follow up. Finally, 50 patients were analyzed for this study.Results: There was no statistically significant difference in mean age, stricture etiology, preoperative stricture length, preoperative IPSS, PVR, and Qmax between groups. There were statistically non-significant findings regarding IPSS and Qmax measured in the 3rd and 7th month but the change in PVR was significant (22.24±25.26 vs 41.13±48.11 ml, p=0.02). UTI occurred significantly higher in group B (23.1% vs 0%, p=0.01) during follow-up in 3rd month. There was no statistically significant difference regarding stricture recurrence between the two groups. A significantly higher proportion (50%) of patients had shown stricture recurrence with stricture length between 1.1-1.5 cm during follow-up. Conclusion: CISC twice weekly after OIU is equally effective regarding stricture recurrence and complications in comparison to the patients doing CISC daily for short-segment stricture. Bangladesh J. Urol. 2023; 26(1): 14-21